The effects of low-volume, high-intensity training on performance parameters in competitive youth swimmers - Nugent, F. N.; Comyns, T.; Nevill, A.; Warrington, G. D. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To assess the effects of a 7-wk low-volume, high-intensity training (HIT) intervention on performance parameters in national-level youth swimmers. Methods: Sixteen swimmers (age 15.8 [1.0] y, age at peak height velocity 12.9 [0.6] y, 100-m freestyle 61.4 [4.1] s) were randomly assigned to an HIT group or a low-intensity, high-volume training (HVT) group that acted as a control. The HIT group reduced their weekly training volume of zone 1 (low-intensity) training by 50% but increased zone 3 (high-intensity) training by 200%. The HVT group performed training as normal. Pretest to posttest measures of physiological performance (velocity at 2.5- and 4-mM blood lactate [velocity 2.5mM and velocity4mM] and peak blood lactate), biomechanical performance (stroke rate, stroke length [SL], and stroke index [SI] over a 50- and 400-m freestyle), and swimming performance (50-, 200-, and 400-m freestyle) were assessed. Results: There were no significant 3-way interactions between time, group, and sex for all performance parameters (P > .05). There was a significant 2-way interaction between time and group for velocity4mM (P = .02, 2 p =.40 Etap2=.40), SL50 (P = .03, Eta2p =.37), and SI50 (P = .03, Eta2 p =.39). Velocity4mM decreased in the HIT group but increased in the HVT group while SL50 and SI50 decreased in the HVT group. Conclusions: A 7-wk HIT intervention was neither beneficial nor detrimental to performance parameters; however, the HIT group completed 6 h (17.0 km) of swimming per week compared with 12 h (33.4 km) per week for the HVT group.